2020
DOI: 10.1098/rsos.200823
|View full text |Cite
|
Sign up to set email alerts
|

Detection and tracking of cracks based on thermoelastic stress analysis

Abstract: Thermoelastic stress analysis using arrays of small, low-cost detectors has the potential to be used in structural health monitoring. However, evaluation of the collected data is challenging using traditional methods, due to the lower resolution of these sensors, and the complex loading conditions experienced. An alternative method has been developed, using image decomposition to generate feature vectors which characterize the uncalibrated map of the magnitude of the thermoelastic effect. Thermal data have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Similarly, the decomposition algorithm only used these areas, with locations containing poor data masked. While this damage monitoring approach has been explored in previous studies [ 25 ], the new damage assessment algorithm increases its readiness for application in industry, where components with complicated shapes are common.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the decomposition algorithm only used these areas, with locations containing poor data masked. While this damage monitoring approach has been explored in previous studies [ 25 ], the new damage assessment algorithm increases its readiness for application in industry, where components with complicated shapes are common.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, the data were not decomposed, instead an optical flow algorithm was used to determine the location of the crack tip as the fatigue crack grew [ 23 ]. In recent work, a technique has been developed that uses Chebyshev decomposition to quantify changes to the stress on the surface of a specimen as it is fatigued [ 25 ]. It would not be possible to directly apply this technique to the data shown in figure 8 as the stress field around the bolts was obscured by the sealant and thus needed to be removed.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by some of the current authors has demonstrated the potential for the original equipment manufacturer (OEM) microbolometers to be used for monitoring cracks under constant amplitude sinusoidal loading [20]. In this work by Middleton et al [20], IR responses to constant amplitude sinusoidal loading were captured using an OEM microbolometer. The acquired data was post-processed to show the crack propagation detection capability of such low-cost bolometers.…”
Section: Introductionmentioning
confidence: 99%